1991
DOI: 10.1139/y91-252
|View full text |Cite
|
Sign up to set email alerts
|

Influences of anabolic androgens on cardiac growth and metabolism in the rat

Abstract: Testosterone, and to a lesser degree methandrostenolone, was shown to influence cardiac growth in immature male rats by affecting protein synthesis and degradation. The nature of cardiac responses to androgen appear to depend on the prevailing experimental conditions. Protein synthesis was inhibited in the castrate rat and was stimulated by subsequent treatment with androgen. Under conditions of induced overgrowth of the ventricles, androgens gave rise to an attenuation of the effects of aortic constriction on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
3

Year Published

1995
1995
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 9 publications
0
12
0
3
Order By: Relevance
“…The heart is a target organ for AAS action; there are receptors with a high affinity for testosterone in myocytes [33], [34]. A well-described positive correlation exists between heart hypertrophy and heart failure that is a major independent risk factor for cardiovascular mortality [35].…”
Section: Discussionmentioning
confidence: 99%
“…The heart is a target organ for AAS action; there are receptors with a high affinity for testosterone in myocytes [33], [34]. A well-described positive correlation exists between heart hypertrophy and heart failure that is a major independent risk factor for cardiovascular mortality [35].…”
Section: Discussionmentioning
confidence: 99%
“…15 16 Additionally, in vivo studies on animal models, performed to show the effects of AAS on the cardiovascular system, detected (1) myocardial structural changes, and (2) cardiac hypertrophy, with both a reduction of response to an inotropic load and an impairment of left ventricular compliance. [12][13][14] However, the effects of chronic misuse of AAS on the athlete's ventricular performance are still under investigation. In fact, some authors have not found any left ventricular functional change in athletes under pharmacological efects of AAS, whereas others have found an initial impairment of the left ventricular diastolic function with an enlargement of the left ventricular chamber and an increase in the thickness of the left ventricular wall.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11] AAS stimulate cellular protein synthesis through androgenic receptors and promote the growth of all organs that have receptors similar to those of androgens. [12][13][14][15][16] The effects of the chronic assumption of AAS on human performance and on cardiovascular structures are subjects of intense debate. Recent bioptical data have shown that in athletes under the pharmacological effects of AAS, a focal increase in myocardial collagen content might occur as a repair mechanism against myocardial damage.…”
mentioning
confidence: 99%
“…Heart During development, cardiac protein synthesis has been shown to be diminished by castration and stimulat ed by subsequent treatment with androgens [31]. How ever, the most prominent hormonal effect on both the heart and its supplying vessels is exerted by thyroxine.…”
Section: Hormonal Effectsmentioning
confidence: 99%